Effect of MgO content in sintered ore on viscosity of blast furnace slag bearing high Al2O3 - F. Yang; Q. F. Qin; Y. Li; Y. Y. Huang; S. P. Wang (Metalurgija, 2024)
The effect of MgO content on the viscosity of blast furnace slag bearing high Al2O3 was studied under laboratory conditions. The viscosity of slag was determined by rotation method. The research results indicate that when the Al2O3 content in blast furnace slag is 17 % -18 %, the MgO content in blast furnace slag should be controlled at 10 %. When the Al2O3 content is 19 %, the MgO content should be controlled at 11 %, and the binary basicity of the slag should be controlled at around 1,10. This type of blast furnace slag has a lower melting point and better fluidity. The purpose of reducing the MgO content in the slag can be achieved by reducing the MgO content in sintered ore, that is, the MgO content in sintered ore should be controlled at 2,0 %-2,5 %.